A priori estimates in terms of the maximum norm for the solution of the Navier-Stokes equations with periodic initial data (The Nepali Mathematical Sciences Report, 2019)
In this paper, we consider the Cauchy problem for the incompressible Navier-Stokes equations in Rn for n ≥ 3 with smooth periodic initial data and derive a priori estimtes of the maximum norm of all derivatives of the solution in terms of the maximum norm of the initial data. This paper is a special case of a paper by H-O Kreiss and J. Lorenz which also generalizes the main result of their paper to higher dimension.